Cover Picture: MnO2 Nanoflower Arrays with High Rate Capability for Flexible Supercapacitors (ChemElectroChem 6/2014. Issue 6 (11th June 2014) - Li, Wenyao; Xu, Kaibing; Li, Bo; Sun, Jianqing; Jiang, Feiran; Yu, Zhishui; Zou, Rujia; Chen, Zhigang; Hu, Junqing
<x xml:space="preserve">Abstract</x> Hu et al. synthesized large‐area α‐MnO2 nanoflower arrays on flexible substrates, which produced a high specific capacitance with remarkable rate capability and excellent cycling stability, as shown on p. 1003.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>